Transformasi Perspektif Hukum Kepailitan dalam Bisnis: Komparasi antara Hukum Positif Indonesia dan Hukum Islam - nurkhalifah; Romi Faslah (Jurnal Ekonomi dan Bisnis Digital, 2025)
This article explores the transformation of bankruptcy law perspectives in Indonesia by comparing the positive legal system with Islamic law. Using a qualitative literature review approach, it examines the potential integration of Islamic values such as substantive justice, mercy (rahmah), and maqaṣid al-shari‘ah into the national bankruptcy framework. The findings show that while Indonesian law emphasizes formal legality and efficiency, Islamic law prioritizes social protection and ethical approaches to debtors. The study recommends reforming Indonesia’s bankruptcy law to be more inclusive, just, and morally grounded through the incorporation of Sharia principles.